Colistin Heteroresistance in Enterobacter cloacae Is Associated with Cross-Resistance to the Host Antimicrobial Lysozyme - Napier, Brooke A. (American Society for Microbiology, 2014)
Here, we describe the first identification of colistin-heteroresistant Enterobacter cloacae in the United States. Treatment of this isolate with colistin increased the frequency of the resistant subpopulation and induced cross-resistance to the host antimicrobial lysozyme. This is the first description of heteroresistance conferring cross-resistance to a host antimicrobial and suggests that clinical treatment with colistin may inadvertently select for bacteria that are resistant to components of the host innate immune system.